Derivation of the static structure factor in strongly coupled non-equilibrium plasmas for X-ray scattering studies - Gregori, G; Ravasio, A; Hoell, A; Glenzer, S; Rose, J (2007)
We present a fully analytical derivation of the static response function in strongly coupled and non-equilibrium plasmas. The model we are proposing is based on a linear response formalism coupled to a charged hard sphere reference for the ions. The electrons, instead, are treated using a local field correction which satisfies the compressibility sum rule at finite temperatures. The model is applied to calculate an effective ion mass that accounts for the self-energy correction of the free particle energy. We will discuss the implication of this approach in the interpretation of experimental results in X-ray scattering measurements from dense plasmas. © 2007 Elsevier B.V. All rights reserved.